2021
DOI: 10.1186/s13014-021-01880-9
|View full text |Cite
|
Sign up to set email alerts
|

Short-course compared to long-course palliative radiotherapy for oesophageal cancer: a single centre observational cohort study

Abstract: Background Common symptoms of oesophageal cancer are dysphagia, pain, and bleeding. These symptoms can be relieved with palliative radiotherapy. The aim of this study was to analyse the outcome of two different palliative radiotherapy schedules. Methods We conducted a retrospective cohort study on palliative radiotherapy for oesophageal cancer given at Karolinska University Hospital. Patients included were treated with either short-course (20 Gy in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The recommended dose for palliation is itself a bit variable, with a range of 20 to 40 Gy across the guidelines. 3 , 4 , 5 , 8 , 13 , 14 , 15 , 16 In the current study, 64.8% of the patients who received radiation received less than 45 Gy, 29% received between 45 and 59.9 Gy, and 2.2% received considerably more radiation (60–80 Gy).…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…The recommended dose for palliation is itself a bit variable, with a range of 20 to 40 Gy across the guidelines. 3 , 4 , 5 , 8 , 13 , 14 , 15 , 16 In the current study, 64.8% of the patients who received radiation received less than 45 Gy, 29% received between 45 and 59.9 Gy, and 2.2% received considerably more radiation (60–80 Gy).…”
Section: Discussionmentioning
confidence: 45%
“…Esophageal stents, cryotherapy, photodynamic therapy, or even cytotoxic chemotherapy may accomplish many of the goals of palliative radiation. 3 , 6 , 7 , 8 , 9 As a result, patient selection must balance possible adverse effects, possible symptomatic improvement, and potential survivorship gains. Better understanding of the current relationship between radiotherapy of the esophagus in newly diagnosed stage IV esophageal cancer and survival may facilitate informed decision making.…”
Section: Introductionmentioning
confidence: 99%
“…However, the retreatment rate in the group receiving a single dose of 8 Gy was much higher than that in the 30 Gy in 10 fractions group (28% vs. 2%). Similarly, Olafsdottir et al [21] found that a short course (20 Gy in 5 fractions) for esophageal cancer had a retreatment rate of 32.0% compared with 18.9% for a long course (30 Gy in 10 fractions). Conversely, Rades et al [22] found that a 1-week course (20 Gy in 5 fractions) and a 2-week course (30 Gy in 10 fractions) for metastatic epidural spinal cord compression were similarly effective in motor function, ambulatory rate, and local progression-free survival and maintained effects for up to 6 months.…”
Section: Discussionmentioning
confidence: 92%
“…Natasja’s and Halla’s study revealed that the dysphagia relief rate showed no difference in patients treated with 30–39 Gy in 10–13 fractions and 20 Gy in 5 fractions [22] , [24] . But there was a long time to second intervention and fewer re-interventions in the higher doses group.…”
Section: Discussionmentioning
confidence: 93%